Analysis of the Extended Technology Acceptance Model as A Basis for the Adoption of Educational Technology Startup Platforms - Fariz; Winarsih, Tutik (Eastasouth Institute, 2025)
The growth of startups in the Educational Technology (EdTech) sector in Indonesia has demonstrated rapid progress, aligning with global advancements in this field. The COVID-19 pandemic, coupled with the increasing demand for future-oriented skills, has driven EdTech startups to innovate in learning methods, approaches, and strategies. These innovations aim to create individuals equipped with skills relevant to the demands of the future. This research seeks to explore how technology-based learning processes developed by EdTech startups can be adapted and utilized by users to enhance their skills in facing the challenges of the modern era. The study adopts the Technology Acceptance Model (TAM) framework with the addition of a facilitating condition variable as an external factor to understand the impact of environmental conditions on technology adoption and usage. A quantitative approach was employed, collecting data from active learners using EdTech startup services in Indonesia during the 2018–2024 period. Data analysis was conducted using Structural Equation Modelling (SEM) techniques. The findings reveal that TAM effectively explains the factors influencing the acceptance and use of e-learning on EdTech startup platforms, particularly in supporting learning processes. Additionally, significant relationships were identified between facilitating conditions, perceived ease of use, and perceived usefulness. The study also confirms the interrelations among the main components of TAM, further reinforcing the model's validity in the context of digital learning.